Gestão das marcas dos clubes de futebol: como o marketing esportivo potencializa o consumo do torcedor - Malagrino, Fernando de Andrade Franco (2011)
Brazilian soccer is entering a new phase, a phase which it can no longer be seen only as a sport, but as a great business that generates revenue of around billions of dollars annually. These revenues derive from different sources: image rights, ticket sales, sale of products, among many others. And these revenues are increasing and fans, like never before, having access to an infinite variety of consumer items, ranging from simple key chains to the possibility of traveling with the team. In the process of change, soccer is no longer the sport of British royalty. It has become the most popular sport in the world. It is within this scenario that this study proposes, on a first level, to examine, through an exploratory qualitative research, soccer clubs and the work they are undertaking to strengthen themselves in the entertainment industry as a brand of expression and, on a second level, through survey with 1,296 respondents, to analyze how the marketing activities undertaken by these clubs are leveraging fans' consumerism. As a result, it is believed that the analysis made in this study supports the notion that changes in soccer industry are profound and altering the foundation of financial support. Fans begin to be seen by their clubs and corporate sponsors as potential consumers eager for products that carry the brand of their beloved teams